Contrast Media-Induced Anaphylaxis Causing a Stress-Related Cardiomyopathy Post Percutaneous Coronary Intervention: Case Report - Rajeev Seecheran; Valmiki Seecheran MBBS; Sangeeta Persad MBBS; Sasha Lalla MBBS; Naveen Anand Seecheran MBBS, MSc, FACC, FESC (SAGE Publishing, 2017)
Anaphylaxis is a sudden-onset, severe hypersensitivity reaction that can be potentially fatal. It can often transition to refractory hemodynamic instability, eventually resulting in death. Stress-related cardiomyopathies (SRCs) have multifactorial etiologies, including being linked to excessive catecholamine release in periods of intense stress. This novel case report recounts a SRC caused by contrast-induced anaphylaxis within 1 hour post percutaneous coronary intervention. Both acutely life-threatening conditions may occur simultaneously and are implicated with devastating complications. Further research is required to understand this cardiac-neuroaxis interplay in SRC to identify risk factors and develop management strategies.